"End-to-end" and "end-to-side” colorectal anastomosis: does the selection of surgical tactics influence insufficiency of the apparatus anastomosis? - Savenkov, D. Yu.; Bielosludtsev, O. D.; Siryi, S. S. (Medicni Perspektivi, 2020)
It is still uncertain whether the choice of “end-to-end” or “end-to-side” anastomosis affects the risk of anastomosis insufficiency, with low anterior resections of the rectum in patients with colorectal cancer. The aim of our work was to determine the influence of choosing the surgical tactics of overlaying colorectal “end-to-end” or “end-to-side” anastomosis on the frequency and severity of the anastomosis leak in patients after rectal resection and postoperative recovery period. A retrospective analysis of the medical documentation of patients after anterior resection of the rectum in relation to rectal cancer was performed. Depending on the type of anastomosis the patients were divided into two groups: group 1 – patients with “end-to-end” anastomosis, group 2 – patients with “end-to-side” anastomosis. Surgical complications including the frequency and severity of intestinal anastomosis leak were analyzed. The total number of postoperative complications among patients in group 1 was by 2 times more frequent than in patients in group 2, and analysis of their severity points on advantage of overlaying “end-to-side” anastomosis. Thus, in 3 (20.0%) patients of group 1 there was a partial failure of anastomosis of the class B, in 2 (13.3%) patients – a partial failure of anastomosis of the class C, in 2 (13.3%) patients there was peritonitis; in 1 (6.7%) patient we found lymphorrhea. While in patients of group 2 there were isolated complications (partial failure of anastomosis of class B was in 2 (14.3%) patients, postoperative seroma was in 2 (14.3%) patients. However, partial failure of anastomosis of class C, peritonitis or lymphorrhea were absent. The number of days from surgery to discharge in patients of group 2 was less (9 [7–13] days compared with 13.0 [9–20] days in patients of group 1). In patients with rectal cancer after anterior rectum resection, the choice of surgical tactics of overlaying of colorectal “end-to-end” or “end-to-side” anastomoses influences the frequency of formation of anastomosis insufficiency; “end-to-side” anastomoses overlay reduces the frequency and severity of the colorectal anastomoses leak, which reduces the postoperative recovery period.